Optimization of thermal regime of continuous CO2-lasers with diffusion cooling - Vasyanovich, A.V.; Gnatenko, A.S.; Pustyl’nikov, D.V. (Radiotekhnika, 2018)
Mathematical methods for optimizing parameters of the CO2 laser, realized using numerical computer simulation, are proposed. The results of numerical calculations coincide with the results of the experimental data, at a partial discrepancy, the reasons associated with the non-optimal consideration of the proposed recombination model on the wall of the O-tube in the reaction O+OW -> O2were established. The results of the work can be fully used to optimize various designs of continuous CO2 lasers.